MEASURES TO COMPLETE THE BASIC TASKS OF THE SKIN-VENEROLOGICAL DISPENSER AND RESULTS OF THE POSSIBLE RISK ANALYSIS TO IMPROVE EFFICIENCY AND EFFICIENCY OF EFFECTIVENESS - Mykhalchuk, V. M.; Gbur, Z. V.; Tolstanov, O. K.; Shchyrina, K. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the scientific article the directions of activity of modern skin and venereological dispensary are described. Measures to improve the work of the institution are proposed: optimization of the number of staff; making changes to the organizational structure in accordance with the new financing and management system; planning, organizing and controlling the activities of the institution within the functions of financial management. The priority measures of reforming the activity of the skin and venereological dispensary were singled out, taking into account the current state of development of the health care system. The main methods of realization of tasks of skin and venereological institutions are given and characterized are administrative, legal, economic, social and motivational. A number of external risks have been identified that could adversely affect the activities of the skin and venereological dispensary, namely: risks related to the situation on the labor market, in particular; risks related to the current state of health care, in particular; risks associated with the medical and demographic crisis in Ukraine.